Market Efficiency within the German Stock Market: A Comparative Study of the Relative Efficiencies of the DAX, MDAX, SDAX and ASE Indices - Admin Starcevic; Timothy Rodgers (International Econometric Review (IER), 2011)
It can be implied from the efficient market hypothesis that the more transparent a market is, then the more likely that the market will be efficient. This paper is a study of whether the different transparency standards applied to the different indices quoted on the German stock market have any impact on their relative efficiencies. It is found that the differences in transparency standards do have an impact on market efficiency. The case for a higher level of market efficiency in respect to Prime Standard index stocks is reinforced by the additional finding that calendar anomaly effects appear to have only limited statistical significance.
Keywords: C10; C12; 330; Market Efficiency; Calendar Anomalies; DAX; Transparency Requirements